Microstructure and Mechanical behavior of Stainless Steel - Pankaj Sonia (International Journal of Advanced Science and Technology, 2020)
The advancement of pipeline industry require high quality corrosion resistance in steel. It will lead a significant worry for countless steel producers. The mechanical properties of stainless steel can be astoundingly improved through reasonable alloying element such as V, Nb and Cr and proper scheduling of thermo-mechanical handling (TMH) parameters that refine and homogenize the microstructure. After complete the process of moving, control of cooling rate is indispensable to shape the necessary stages in the last microstructure. Present examination plans to consider the impact of cooling rate and thermo-mechanical handling parameters on the microstructure and mechanical properties of stainless steel. The characterization study is carried out on optical, SEM and Transmission electron microscopy (TEM). The experiment shows that improvement in grain refinement and precipitation density dispersion.